Diagnostic Instruments and Therapeutic Decisions in Velopharyngeal Dysfunction of Pediatric Patients - Maja Solarz; Barbara Jarzemska; Dorota Gabrowska; Józef Mierzwiński (Logopedia)
Velopharyngeal dysfunction (VPD) is a disorder of the function of the velopharyngeal valve, whose task is to separate the nasal cavity from the oral cavity during the act of speech, blowing, sucking or vomiting. Incorrect sphincter function can lead to incomprehensible speech (open nasal speech) and leakage of air and fluid into the nasal cavities. The dysfunction also adversely affects the swallowing process and the ventilation of the middle ear. This study describes the anatomical and pathophysiological basis of this disease and takes into account the difficult diagnostic process as well as the treatment of the described problem. When evaluating patients, both before and after treatment, scales should be used to objectiveize the symptoms presented by children with the described dysfunction. The proposed procedure takes into account the author’s diagnostic elements (a selected speech sample), developed by the authors for the needs of treatment of patients with VPD adapted to the Polish language. The proposed diagnostic and therapeutic scheme has been used in practice in the authors’ center for several years. Therapeutic management was described depending on the severity of symptoms, as well as methods of assessing dysfunction and treatment results. In order to obtain optimal treatment results, close cooperation between laryngologists/pediatric surgeons, phoniatrists and speech therapists is necessary.